A method for improving the coercivity of samarium cobalt magnets by ultra-high pressure pre-aging treatment
Through ultra -high -pressure pre -efficiency processing technology to regulate the stress and defects of mandile cobalt alloys, the problem of high -FE content of cobalt magnetic stubborn power is solved, and the stubborn power is greatly improved.
Patent Information
- Application Number
- CN202410198549.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-02-22
AI Technical Summary
When the Fe content of 2:17 type samarium cobalt magnet with high Fe content is close to or exceeding 20 wt%, the coercive force is low, making it difficult to effectively form a cellular structure, which limits its development.
Ultra-high pressure pre-aging treatment technology is used to regulate the stress and microscopic defects in the samarium-cobalt alloy to affect the formation of the 1:5 samarium-cobalt cell wall phase during the later aging process, thereby improving the coercive force of the samarium-cobalt magnet. The specific steps include smelting metal raw materials into ingots, crushing into alloy powder, molding, cold isostatic pressing, sintering and solid solution treatment, followed by high-pressure pre-aging treatment using a six-sided top press, and finally conventional aging treatment.
Through this method, the orthodontic power of the FE content of 19.5WT % to 21.5WT % increased by 15.3 % to 79.3 %, which significantly enhanced the magnetic resistance of the magnet.
Smart Images

Figure CN118156014B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of rare earth permanent magnet materials, and in particular to a method for improving the coercive force of samarium cobalt magnets by using ultra-high pressure pre-aging treatment. Background Art
[0002] Bulk permanent magnetic materials play a huge role in modern science and technology and industrial applications. Permanent magnetic materials usually have strong magnetism. The characteristic is that they can still maintain permanent magnetism after being magnetized to saturation by an external magnetic field and then removing the external magnetic field. As a renewable resource, permanent magnetic materials are energy-saving, efficient and compact. Nowadays, electronic devices are developing towards miniaturization and micro-miniaturization, so the magnetic properties of rare earth permanent magnetic materials are increasingly required. The development of high-performance rare earth permanent magnetic materials has gone through three generations: SmCo5, Sm2Co 17 and Nd2Fe 14 B. These three generations of rare earth permanent magnet materials have developed into an important material basis for national economy and national defense construction, and play an irreplaceable role in electronic equipment and magnetic sensors, electric vehicles, nuclear magnetic resonance, aerospace and other fields. The second generation 2:17 type samarium cobalt permanent magnet material has the advantages of high Curie temperature, high magnetic energy product, good corrosion resistance and thermal stability. It can still work normally in high temperature environments exceeding 400°C, and is the most important high temperature permanent magnet.
[0003] The magnetic energy product is an important parameter to measure the amount of energy stored in a magnet. As we all know, the maximum theoretical magnetic energy product of a magnet is proportional to the saturation magnetization intensity M. s The square of the saturation magnetization intensity can be used to obtain a higher energy product. At present, in order to obtain a 2:17 type samarium cobalt magnet with a higher energy product, the main method used is to replace Co atoms with Fe with a high atomic magnetic moment. This can not only improve the theoretical energy product, but also reduce the cost of raw materials, which is an important development direction in this field. When the mass fraction of Fe is in the range of 15% to 20%, Sm2Co 17 It has excellent comprehensive properties; however, the increase in Fe content is often accompanied by a decrease in coercivity. When the mass fraction of Fe is close to or exceeds 20%, the cellular structure of this type of magnet is difficult to form effectively, which leads to a sharp decrease in coercivity, which seriously limits the development of high-Fe samarium cobalt magnets.
[0004] Coercivity is one of the most important magnetic parameters and an important physical quantity to measure the anti-demagnetization ability of magnets. High coercivity is the key to maintaining high stability of magnets in service environments. In the use of magnets, the higher the coercivity of the magnets, the better the temperature stability. The second-generation 2:17 samarium cobalt permanent magnet material is a precipitation-strengthened compound, and its excellent performance comes from the unique cell wall structure: intracellular phase, cell wall phase and lamellar phase. The intracellular phase is a Fe-rich rhombohedral structure 2:17R main phase, which is the source of the high saturation magnetization intensity of the magnet; the cell wall phase is a Cu-rich hexagonal structure 1:5H phase, and the cell wall phase provides high coercivity of the magnet through domain wall pinning.
[0005] At present, in addition to adjusting the original composition ratio, the coercivity is generally improved by improving the isothermal aging process to promote the formation of the precipitated phase. For example, the coercivity of the magnet is improved by extending the aging time or graded aging, or by introducing an intermediate pre-aging process. However, after the Fe content increases, such as when the Fe content is close to or exceeds 20wt%, the coercivity of the samarium cobalt magnet is generally low. Therefore, there is an urgent need for a method that can effectively improve the coercivity of this type of magnet. Summary of the invention
[0006] The embodiment of the present application provides a method for improving the coercive force of a samarium cobalt magnet by using an ultra-high pressure pre-aging treatment. By regulating the stress and microscopic defects in the samarium cobalt alloy, the formation of a samarium cobalt 1:5 cell wall phase during the later aging process is affected, so that the coercive force of the samarium cobalt magnet is greatly improved.
[0007] To solve the above technical problems, an embodiment of the present application provides a method for improving the coercive force of a samarium cobalt magnet by ultra-high pressure pre-aging treatment, the method comprising the following steps: first, placing metal raw materials in a vacuum induction furnace according to a ratio for smelting to obtain an ingot, and crushing the ingot to obtain an alloy powder; then, the alloy powder is molded in a magnetic field, and a green body is obtained by cold isostatic pressing; the green body is sintered and solution treated to obtain a samarium cobalt magnet in a solid solution state; next, the samarium cobalt magnet in a solid solution state is pre-aged by a six-sided top press; finally, the sample after the pre-aging treatment is subjected to a first aging treatment and a second aging treatment in sequence to obtain a samarium cobalt magnet.
[0008] In some exemplary embodiments, the sample after pre-aging treatment is placed in a muffle furnace, and the first aging treatment and the second aging treatment are performed in sequence; wherein the temperature of the first aging treatment is 840°C, and the aging time is 10 hours; the temperature of the second aging treatment is 400°C, and the aging time is 1 hour to 10 hours.
[0009] In some exemplary embodiments, during the first step of aging treatment, the heating process is: from 0°C to 790°C at a heating rate of 5°C / min, the time is 158 minutes; from 790°C to 830°C at a heating rate of 2°C / min, the time is 20 minutes; from 830°C to 840°C at a heating rate of 1°C / min, the time is 10 minutes.
[0010] In some exemplary embodiments, after the first aging treatment, the temperature is lowered to 400° C. at a cooling rate of 0.7° C. / min for a second aging treatment; after the second aging treatment, the furnace is cooled to room temperature to obtain a samarium cobalt magnet.
[0011] In some exemplary embodiments, the pre-aging treatment has a pressure of 1.0 GPa to 1.5 GPa, a temperature of 650° C. to 750° C., and a heat and pressure holding time of 30 min to 60 min.
[0012] In some exemplary embodiments, after the heat preservation and pressure preservation are completed, the heating is stopped and the pressure is reduced to 0 before the sample is taken out to complete the pre-aging treatment.
[0013] In some exemplary embodiments, the metal raw materials are industrial Sm, Co, Cu, Fe, and Zr with a purity of more than 99.5wt%, and the metal raw materials are placed in a medium-frequency vacuum induction furnace according to a proportion, and smelted under argon protection to form a high-Fe alloy ingot; the alloy composition of the high-Fe alloy ingot is Sm 25 Co bla Fe x Cu 5.6 Zr 3.0 (x=19.5wt.%~23.5wt.%).
[0014] In some exemplary embodiments, the preparation process of the solid solution samarium cobalt magnet includes: press-forming the coarsely crushed and ball-milled alloy powder in a magnetic field of >10kOe, and forming a green embryo by cold isostatic pressing at 200MPa; sintering the green embryo at 1180℃~1200℃ for 60min~90min under argon protection, and then solution treating at 1150℃~1170℃ for 60min to obtain a solid solution samarium cobalt magnet.
[0015] In some exemplary embodiments, after obtaining a solid solution samarium cobalt magnet and before performing a pre-aging treatment on the solid solution samarium cobalt magnet using a six-sided top press, the method further includes: cutting the solid solution samarium cobalt magnet into cylindrical samples using wire cutting; polishing the surface of the cylindrical sample with sandpaper until it is smooth and completely coating it with a 0.01 mm thick foil, then placing it in boron nitride powder for pressure molding, placing talc in it, and performing a pre-aging treatment using a six-sided top press.
[0016] In some exemplary embodiments, the cylindrical sample has a specification of 5 mm in diameter and 2 mm in height.
[0017] The technical solution provided by the embodiments of the present application has at least the following advantages:
[0018] The embodiment of the present application provides a method for improving the coercive force of a samarium cobalt magnet by using an ultra-high pressure pre-aging treatment, and the method comprises the following steps: first, placing metal raw materials in a vacuum induction furnace according to a ratio for smelting to obtain an ingot, and crushing the ingot to obtain an alloy powder; then, the alloy powder is molded in a magnetic field, and a green body is obtained by cold isostatic pressing; the green body is sintered and solution treated to obtain a samarium cobalt magnet in a solid solution state; next, the samarium cobalt magnet in a solid solution state is pre-aged by using a six-sided top press; finally, the sample after the pre-aging treatment is subjected to a first aging treatment and a second aging treatment in sequence to obtain a samarium cobalt magnet. The present application selects a solid solution 2:17 type samarium cobalt magnet with an Fe content of 19.5wt% to 21.5wt%, adopts a six-sided top press high pressure technology, and performs high pressure pre-aging for 30min to 60min on the solid solution sample at a pressure of 1.0GPa to 1.5GPa and a temperature of 650℃ to 750℃; then, the high pressure pre-aging sample is subjected to conventional aging treatment to obtain a 2:17 type samarium cobalt magnet with high coercivity. Compared with the sample without high pressure pre-aging treatment, the coercivity of the samarium cobalt alloy treated with high pressure pre-aging for 30min to 60min, 650℃ to 750℃, and 1.0GPa to 1.5GPa is increased by 15.3% to 79.3%. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplified descriptions do not constitute limitations on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute proportional limitations.
[0020] Figure 1 A schematic flow chart of a method for improving the coercive force of samarium cobalt magnets by ultrahigh pressure pre-aging treatment provided in one embodiment of the present application.
[0021] Figure 2 This is the demagnetization curve of the sample after aging in Example 1 of the present application.
[0022] Figure 3 This is the demagnetization curve of the sample after aging in Example 2 of the present application.
[0023] Figure 4 This is the demagnetization curve of the sample after aging in Example 3 of the present application.
[0024] Figure 5 This is the demagnetization curve of the sample after aging in Example 4 of the present application.
[0025] Figure 6 This is the demagnetization curve of the sample after aging in Example 5 of the present application.
[0026] Figure 7 It is the demagnetization curve of comparative example 1 of the present application.
[0027] Figure 8 This is the demagnetization curve of the sample after aging in Example 6 of the present application.
[0028] Fig. 9 This is the demagnetization curve of the sample after aging in Example 7 of the present application.
[0029] Fig.10 This is the demagnetization curve of comparative example 2 of the present application. DETAILED DESCRIPTION
[0030] As can be seen from the background technology, the coercivity is improved by adjusting the original composition ratio and improving the isothermal aging process to promote the formation of the precipitated phase. However, after the Fe content increases, the coercivity of the samarium cobalt magnet is generally low. Therefore, there is an urgent need for a method that can effectively improve the coercivity of this type of magnet.
[0031] Pressure is an important parameter for regulating phase change. In recent years, people have begun to pay attention to how to use high pressure to control the structure and magnetism of 2:17 type samarium cobalt permanent magnet materials. Patent document CN201811060403.X generates ultra-high pressure of 900MPa to 1100MPa through Ar gas during magnet sintering (1000℃~1010℃), solid solution (980℃~990℃) and tempering (780℃~790℃, i.e., aging process), thereby obtaining a magnet with high coercivity, but the patent does not mention the Fe content in the sample. Patent document CN201910671594.1 generates an ultra-high pressure of 900MPa to 1100MPa through Ar gas during the pre-tempering and tempering (i.e., pre-aging and aging) of magnets with an Fe content of 15wt% to 15.8wt%. The pre-tempering temperature is 720℃ to 740℃, and the tempering temperature is not given, thereby obtaining a magnet with high coercive force. Patent document 202110244313.1 applies a long period of high pressure (30MPa to 100MPa) to the aging process (810℃ to 850℃) of this type of magnet, thereby obtaining a magnet with high coercive force. It can be seen from the above technical scheme that high pressure and ultra-high pressure can have an important influence on the structure and magnetism of 2:17 type samarium cobalt permanent magnet materials. However, at present, there is still a lack of effective methods for regulating the coercive force of samarium cobalt magnets with high Fe content.
[0032] In order to solve the above technical problems, the embodiment of the present application provides a method for improving the coercive force of samarium cobalt magnets by ultra-high pressure pre-aging treatment, and the method comprises the following steps: first, placing the metal raw materials in a vacuum induction furnace according to the proportion to obtain an ingot, and crushing the ingot to obtain an alloy powder; then, the alloy powder is molded in a magnetic field, and a green body is obtained by cold isostatic pressing; after the green body is sintered and solution treated, a solid solution state samarium cobalt magnet is obtained; next, the solid solution state samarium cobalt magnet is subjected to pre-aging treatment by a six-sided top press; finally, the sample after pre-aging treatment is subjected to the first step aging treatment and the second step aging treatment in sequence to obtain a samarium cobalt magnet. The embodiment of the present application provides a method for improving the coercive force of samarium cobalt magnets by ultra-high pressure pre-aging treatment, which greatly improves the coercive force of samarium cobalt magnets by regulating the stress and microscopic defects in the samarium cobalt alloy, thereby affecting the formation of the samarium cobalt 1:5 cell wall phase during the later aging process.
[0033] The following will describe the various embodiments of the present application in detail with reference to the accompanying drawings. However, it will be appreciated by those skilled in the art that in the various embodiments of the present application, many technical details are provided in order to enable the reader to better understand the present application. However, even without these technical details and various changes and modifications based on the following embodiments, the technical solution claimed in the present application can be implemented.
[0034] See also Figure 1 The present application provides a method for improving the coercivity of a samarium cobalt magnet by ultrahigh pressure pre-aging treatment, comprising the following steps:
[0035] Step S1, placing metal raw materials according to proportion in a vacuum induction furnace to smelt to obtain ingots, and crushing the ingots to obtain alloy powders.
[0036] Step S2, molding the alloy powder in a magnetic field, and obtaining a green body by cold isostatic pressing; sintering and solution treating the green body to obtain a solid solution samarium cobalt magnet.
[0037] Step S3: using a six-sided top press to perform a pre-aging treatment on the solid solution state samarium cobalt magnet.
[0038] Step S4, subjecting the sample after the pre-aging treatment to the first aging treatment and the second aging treatment in sequence to obtain a samarium cobalt magnet.
[0039] In some embodiments, in step S4, the sample after pre-aging treatment is placed in a muffle furnace, and the first step aging treatment and the second step aging treatment are performed in sequence; wherein, the temperature of the first step aging treatment is 840°C, and the aging time is 10 hours; the temperature of the second step aging treatment is 400°C, and the aging time is 1 hour to 10 hours.
[0040] In some embodiments, during the first step of aging treatment, the heating process is: from 0°C to 790°C at a heating rate of 5°C / min, the time is 158 minutes; from 790°C to 830°C at a heating rate of 2°C / min, the time is 20 minutes; from 830°C to 840°C at a heating rate of 1°C / min, the time is 10 minutes.
[0041] In some embodiments, after the first aging treatment, the temperature is lowered to 400° C. at a cooling rate of 0.7° C. / min for a second aging treatment; after the second aging treatment, the temperature is cooled to room temperature in the furnace to obtain a samarium cobalt magnet.
[0042] In some embodiments, the pre-aging treatment has a pressure of 1.0 GPa to 1.5 GPa, a temperature of 650° C. to 750° C., and a heat and pressure holding time of 30 min to 60 min.
[0043] In some embodiments, after the heat preservation and pressure preservation are completed, the heating is stopped and the pressure is reduced to 0 before the sample is taken out to complete the pre-aging treatment.
[0044] Step S1 and step S2 are mainly used for processing metal raw materials. In some embodiments, the metal raw materials in step S1 are industrial Sm, Co, Cu, Fe, and Zr with a purity of more than 99.5wt%, and the metal raw materials are placed in a medium-frequency vacuum induction furnace according to a ratio, and smelted under argon protection to form a high-Fe alloy ingot; the alloy composition of the high-Fe alloy ingot is Sm 25 Co bla Fe x Cu 5.6 Zr 3.0 (x=19.5wt.%~23.5wt.%).
[0045] In some embodiments, the preparation process of the solid solution samarium cobalt magnet in step S2 includes: pressurizing the coarsely crushed and ball-milled alloy powder in a magnetic field of >10kOe, and forming a green embryo by cold isostatic pressing at 200MPa; sintering the green embryo at 1180℃~1200℃ for 60min~90min under argon protection, and then solution treating at 1150℃~1170℃ for 60min to obtain a solid solution samarium cobalt magnet.
[0046] In some embodiments, after obtaining the solid solution samarium cobalt magnet in step S2, before the solid solution samarium cobalt magnet is subjected to pre-aging treatment by a six-sided top press in step S3, it also includes: cutting the solid solution samarium cobalt magnet into cylindrical samples by wire cutting; polishing the surface of the cylindrical sample with sandpaper until smooth and completely covering it with a 0.01mm thick foil, then placing it in boron nitride powder for press molding, placing pyrophyllite in it, and performing pre-aging treatment by a six-sided top press. The specific parameters are: pressure 1.0GPa~1.5GPa, temperature 650℃~750℃, heat preservation and pressure holding time of 30min~60min, then stopping heating and releasing pressure, and taking out the sample.
[0047] In some embodiments, the cylindrical sample has the following specifications: 5 mm in diameter and 2 mm in height.
[0048] After pre-aging treatment with a six-sided top press, the pre-aging treated sample was placed in a muffle furnace for aging treatment. First, the temperature was raised from 0°C to 790°C at a heating rate of 5°C / min for 158 minutes; then the temperature was raised from 790°C to 830°C at a heating rate of 2°C / min for 20 minutes; then the temperature was raised from 830°C to 840°C at a heating rate of 1°C / min for 10 minutes; then the temperature was kept at 840°C for 10 hours; then the temperature was lowered to 400°C at a cooling rate of 0.7°C / min for secondary aging, and the secondary aging time was 1 to 10 hours. The samarium cobalt magnet was obtained by cooling to room temperature with the furnace.
[0049] Finally, the samples after aging treatment were processed and tested. Specifically, the samples after aging treatment were cut into small cylinders by wire cutting, polished with sandpaper to a diameter and height of about 1 mm, and the hysteresis loop of the magnet was measured by a comprehensive physical property measurement system (PPMS).
[0050] The method for improving the coercive force of samarium cobalt magnets by ultra-high pressure pre-aging treatment provided by the present application is described in detail below through specific embodiments.
[0051] Example 1
[0052] (1) High-pressure pre-aging was performed using a six-sided top press. A 2:17 type samarium cobalt magnet with a solid solution state and an Fe content of 21.5% was taken and cut into a cylinder with a diameter of 5 mm and a height of 2 mm using a wire cutting machine. The sample was polished and completely wrapped with a 0.01 mm thick foil. The wrapped sample was placed in boron nitride powder and pressed into a cylinder with a height of 16 mm and a diameter of 11 mm. The cylinder was placed in a graphite sleeve and covered with pyrophyllite. A conductive steel cap with a diameter of 14 mm and a height of 6 mm was placed on the top and bottom, respectively, to ensure that the cumulative height of the graphite sleeve and the steel cap was equal to the height of the pyrophyllite. The sample loaded with pyrophyllite was placed at the angle between the three base top hammers so that the steel cap fits tightly with the front and rear top hammers. After the six sides of the six-sided top hydraulic press applied a pressure of 1 GPa, the sample temperature was raised from room temperature to 650°C within 6 minutes by controlling the heating power, and then kept warm and under pressure for 60 minutes; after that, the heating was stopped and the pressure was reduced to 0, and the sample was taken out to complete the pre-aging.
[0053] (2) The pre-aged samples were subjected to conventional aging treatment, specifically: the temperature was increased from 0°C to 790°C at a heating rate of 5°C / min for 158 min; then the temperature was increased from 790°C to 830°C at a heating rate of 2°C / min for 20 min; then the temperature was increased from 830°C to 840°C at a heating rate of 1°C / min for 10 min; then heat treated at 840°C for 10 h; finally, the temperature was reduced to 400°C at a cooling rate of 0.7°C / min for secondary aging, and then cooled to room temperature in the furnace after keeping the temperature for 1 hour.
[0054] (3) The magnetic properties of the samples after aging were tested to obtain magnets with higher magnetic properties (H ci =22.05kOe, B r =11.91kGs, (BH) max =27.00MGOe). Figure 2 is the demagnetization curve of the sample after aging in Example 1 of the present application. Compared with the sample without high voltage pre-aging ( Figure 7 ) compared with the original material, the coercivity increased by 79.3%.
[0055] Example 2
[0056] (1) High-pressure pre-aging is performed using a six-sided top press. Take a 2:17 type samarium cobalt magnet with a solid solution state and an Fe content of 21.5%. The sample assembly is the same as step 1 of Example 1. After the six sides of the six-sided top hydraulic press apply a pressure of 1 GPa, the power is controlled to increase the sample temperature. After 7 minutes, the sample temperature rises from room temperature to 700°C, and then the temperature and pressure are maintained for 60 minutes to complete the pre-aging.
[0057] (2) The pre-aged samples were subjected to conventional aging treatment, specifically: the temperature was increased from 0°C to 790°C at a heating rate of 5°C / min for 158 min; then the temperature was increased from 790°C to 830°C at a heating rate of 2°C / min for 20 min; then the temperature was increased from 830°C to 840°C at a heating rate of 1°C / min for 10 min; then the sample was heat treated at 840°C for 10 h; finally, the sample was cooled to 400°C at a cooling rate of 0.7°C / min for secondary aging, and then cooled to room temperature after keeping the temperature for 5 hours.
[0058] (3) The magnetic properties of the samples after aging were tested to obtain magnets with higher magnetic properties (H ci =21.02kOe, B r =11.82kGs, (BH) max =23.59MGOe). Figure 3 is the demagnetization curve of the sample after aging in Example 2 of the present application. Compared with the sample without high voltage pre-aging ( Figure 7 ) compared with the original material, the coercivity increased by 70.9%.
[0059] Embodiment 3:
[0060] (1) High-pressure pre-aging is performed using a six-sided top press. Take a 2:17 type samarium cobalt magnet with a solid solution state and an Fe content of 21.5%. The sample assembly is the same as step 1 of Example 1. After the six sides of the six-sided top hydraulic press apply pressure to 1GPa, the power is controlled to increase the sample temperature. After 7 minutes, the sample temperature rises from room temperature to 750°C, and then the temperature and pressure are maintained for 60 minutes to complete the pre-aging.
[0061] (2) The pre-aged samples were subjected to conventional aging treatment, specifically: the temperature was increased from 0°C to 790°C at a heating rate of 5°C / min for 158 min; then the temperature was increased from 790°C to 830°C at a heating rate of 2°C / min for 20 min; then the temperature was increased from 830°C to 840°C at a heating rate of 1°C / min for 10 min; then the sample was heat treated at 840°C for 10 h; finally, the sample was cooled to 400°C at a cooling rate of 0.7°C / min for secondary aging, and then cooled to room temperature after keeping the temperature for 10 h.
[0062] (3) The magnetic properties of the samples after aging were tested to obtain magnets with higher magnetic properties (H ci =19.34kOe, B r =11.83kGs, (BH) max =28.72MGOe). Figure 4 is the demagnetization curve of the sample after aging in Example 3 of the present application. Compared with the sample without high voltage pre-aging ( Figure 7 ) compared with the original material, the coercivity increased by 57.2%.
[0063] Embodiment 4:
[0064] (1) High-pressure pre-aging is performed using a six-sided top press. Take a 2:17 type samarium cobalt magnet with a solid solution state and an Fe content of 21.5%. The sample assembly is the same as step 1 of Example 1. After the six sides of the six-sided top hydraulic press apply pressure to 1.0GPa, the power is controlled to increase the sample temperature. After 7 minutes, the sample temperature rises from room temperature to 750°C, and then the temperature and pressure are maintained for 30 minutes to complete the pre-aging.
[0065] (2) Performing conventional aging treatment on the pre-aged sample, the specific process is the same as step 2 of Example 1.
[0066] (3) The magnetic properties of the samples after aging were tested to obtain magnets with higher magnetic properties (H ci =15.20kOe, B r =11.89kGs, (BH) max =29.66MGOe). Figure 5 is the demagnetization curve of the sample after aging in Example 4 of the present application. Compared with the sample without high voltage pre-aging ( Figure 7 ) compared with the original material, the coercivity increased by 23.6%.
[0067] Embodiment 5:
[0068] (1) High-pressure pre-aging is performed using the six-sided top high-pressure (HP) technology. Take a solid solution 2:17 type samarium cobalt magnet with an Fe content of 21.5%, and the sample assembly is the same as step (1) of Example 1. After the six sides of the six-sided top hydraulic press apply pressure to 1.5GPa, the power is controlled to increase the sample temperature. After 7 minutes, the sample temperature rises from room temperature to 750°C, and then the temperature and pressure are maintained for 60 minutes to complete the pre-aging.
[0069] (2) Performing conventional aging treatment on the pre-aged sample, the specific process is the same as step 2 of Example 1.
[0070] (3) The magnetic properties of the samples after aging were tested to obtain magnets with higher magnetic properties (H ci =19.46kOe, B r =11.97kGs, (BH) max =29.55MGOe). Figure 6 is the demagnetization curve of the sample after aging in Example 5 of the present application. Compared with the sample without high voltage pre-aging ( Figure 7 ) compared with the original material, the coercivity increased by 58.2%.
[0071] Comparative Example 1:
[0072] (1) Take a solid solution 2:17 type samarium cobalt magnet with an Fe content of 21.5%, and cut it into a cylinder with a diameter of 5 mm and a height of 2 mm by wire cutting. The sample is subjected to conventional aging treatment, and the specific process is the same as step 2 of Example 1.
[0073] (2) The magnetic properties of the aged samples were tested and the magnetic properties were (H ci =12.30kOe, B r =11.90kGs, (BH) max =30.08MGOe). Figure 7 It is the demagnetization curve of comparative example 1 of the present application.
[0074] Embodiment 6:
[0075] (1) High-pressure pre-aging is performed using the six-sided top high-pressure (HP) technology. Take a solid solution 2:17 type samarium cobalt magnet with an Fe content of 19.5%, and the sample assembly is the same as step 1 of Example 1. After the six sides of the six-sided top hydraulic press apply pressure to 1GPa, the power is controlled to increase the sample temperature. After 7 minutes, the sample temperature rises from room temperature to 750°C, and then the temperature and pressure are maintained for 60 minutes to complete the pre-aging.
[0076] (2) Performing conventional aging treatment on the pre-aged sample, the specific process is the same as step 2 of Example 1.
[0077] (3) The magnetic properties of the samples after aging were tested to obtain magnets with higher magnetic properties (H ci =23.35kOe, B r =11.69kGs, (BH) max =29.50MGOe). Figure 8 is the demagnetization curve of the sample after aging in Example 6 of the present application. Compared with the sample without high voltage pre-aging ( Fig.10 ) compared with the original material, the coercivity increased by 29.0%.
[0078] Embodiment 7:
[0079] (1) High-pressure pre-aging is performed using the six-sided top high-pressure (HP) technology. Take a solid solution 2:17 type samarium cobalt magnet with an Fe content of 19.5%, and the sample assembly is the same as step 1 of Example 1. After the six sides of the six-sided top hydraulic press apply pressure to 1GPa, the power is controlled to increase the sample temperature. After 7 minutes, the sample temperature rises from room temperature to 750°C, and then the temperature and pressure are maintained for 30 minutes to complete the pre-aging.
[0080] (2) Performing conventional aging treatment on the pre-aged sample, the specific process is the same as step 2 of Example 1.
[0081] (3) The magnetic properties of the samples after aging were tested to obtain magnets with higher magnetic properties (Hci =20.87kOe, B r =11.60kGs, (BH) max =28.98MGOe). Fig. 9 is the demagnetization curve of the sample after aging in Example 7 of the present application. Compared with the sample without high voltage pre-aging ( Fig.10 ) compared with the original material, the coercivity increased by 15.3%.
[0082] Comparative Example 2:
[0083] (1) Take a solid solution 2:17 type samarium cobalt magnet with an Fe content of 19.5%, and cut it into a cylinder with a diameter of 5 mm and a height of 2 mm by wire cutting. The sample is subjected to conventional aging treatment, and the specific process is the same as step 2 of Example 1.
[0084] (2) The magnetic properties of the aged samples were tested and the magnetic properties were (H ci =18.1kOe, B r =11.70kGs, (BH) max =30.62MGOe). Fig.10 This is the demagnetization curve of comparative example 2 of the present application.
[0085] The magnetic properties of the above-mentioned example samples and comparative example samples of the present application are compared as shown in Table 1 below.
[0086] Table 1 Comparison of magnetic properties between example samples and comparative example samples
[0087]
[0088] According to the above technical scheme, the embodiment of the present application provides a method for improving the coercivity of samarium cobalt magnets by ultra-high pressure pre-aging treatment, and the method includes the following steps: first, placing the metal raw materials in a vacuum induction furnace according to the proportion to obtain an ingot, and crushing the ingot to obtain an alloy powder; then, the alloy powder is molded in a magnetic field, and a green body is obtained by cold isostatic pressing; after the green body is sintered and solution treated, a solid solution samarium cobalt magnet is obtained; next, the solid solution samarium cobalt magnet is subjected to pre-aging treatment by a six-sided top press; finally, the sample after pre-aging treatment is subjected to the first step aging treatment and the second step aging treatment in sequence to obtain a samarium cobalt magnet. The present application uses a six-sided top to directly load a pressure of 1.0GPa to 1.5GPa on the sample, and performs aging treatment at the same time. Compared with the prior art that proposes an inert gas to provide an ultra-high pressure environment, it has obvious innovations, and at the same time couples the two conditions of high pressure and aging, greatly improving the coercivity.
[0089] The present application selects a solid solution 2:17 type samarium cobalt magnet with an Fe content of 19.5wt% to 21.5wt%, adopts a six-sided top press high pressure technology, and performs high pressure pre-aging for 30min to 60min on the solid solution sample at a pressure of 1.0GPa to 1.5GPa and a temperature of 650℃ to 750℃; then, the high pressure pre-aging sample is subjected to conventional aging treatment to obtain a 2:17 type samarium cobalt magnet with high coercivity. Compared with the sample without high pressure pre-aging treatment, the coercivity of the samarium cobalt alloy treated with high pressure pre-aging for 30min to 60min, 650℃ to 750℃, and 1.0GPa to 1.5GPa is increased by 15.3% to 79.3%.
[0090] This application proposes for the first time to use high pressure as a thermodynamic parameter to regulate the structure and magnetism of samarium cobalt alloys, which is completely different from the traditional method of mainly relying on composition design and heat treatment temperature and time to regulate the structure and magnetism of this type of magnet, and has a good development space and market prospects. This application uses the ultra-high pressure (1.0GPa~1.5GPa) generated by a conventional six-sided top press to pre-age samarium cobalt magnets with a high Fe content of 19.5wt%~21.5wt%. This process can be used to regulate the stress and defects in the sample before the aging process, and then regulate the microstructure and magnetism of the final sample, especially the substantial increase in coercive force. This application is significantly different from the coercive force regulation of low Fe content magnets in existing samarium cobalt high pressure related patents and reports, and is also significantly different from the normal pressure pre-aging process or low pressure long-term aging process for samarium cobalt magnets.
[0091] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes can be made to them in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art can make their own changes and modifications without departing from the spirit and scope of the present application, so the scope of protection of the present application shall be based on the scope defined in the claims.
Claims
1. A method for improving the coercivity of samarium cobalt magnets by ultra-high pressure pre-aging treatment, characterized in that: The following steps are involved: The metal raw materials are placed in a vacuum induction furnace according to a proportion to obtain an ingot, and the ingot is crushed to obtain an alloy powder; the alloy powder is molded in a magnetic field, and a green body is obtained by cold isostatic pressing; the green body is sintered and solution treated to obtain a solid solution samarium cobalt magnet; the Fe content of the solid solution samarium cobalt magnet is 19.5wt% to 21.5wt%; The solid solution samarium cobalt magnet is subjected to a pre-aging treatment by using a six-sided top press; the pre-aging treatment is performed at a pressure of 1.0 GPa to 1.5 GPa, a temperature of 650° C. to 750° C., and a heat and pressure holding time of 30 min to 60 min; The sample after the pre-aging treatment is subjected to the first-step aging treatment and the second-step aging treatment in sequence to obtain a samarium cobalt magnet.
2. The method for improving the coercivity of samarium cobalt magnets by ultrahigh pressure pre-aging treatment according to claim 1, characterized in that: The sample after pre-aging treatment is placed in a muffle furnace, and the first step aging treatment and the second step aging treatment are carried out in sequence; wherein, the temperature of the first step aging treatment is 840°C, and the aging time is 10h; the temperature of the second step aging treatment is 400°C, and the aging time is 1h to 10h.
3. The method for improving the coercivity of samarium cobalt magnets by ultrahigh pressure pre-aging treatment according to claim 1, characterized in that: In the first step of aging treatment, the heating process is: The temperature was raised from 0°C to 790°C at a rate of 5°C / min for 158 min; The temperature was raised from 790°C to 830°C at a heating rate of 2°C / min for 20 min; The temperature was raised from 830°C to 840°C at a heating rate of 1°C / min for 10 min.
4. The method for improving the coercivity of samarium cobalt magnets by ultrahigh pressure pre-aging treatment according to claim 1, characterized in that: After the first aging treatment, the temperature was lowered to 400°C at a cooling rate of 0.7°C / min for the second aging treatment; After the second aging treatment, the steel is furnace cooled to room temperature to obtain a samarium cobalt magnet.
5. The method for improving the coercivity of samarium cobalt magnets by ultrahigh pressure pre-aging treatment according to claim 3, characterized in that: After the heat preservation and pressure preservation are completed, the heating is stopped and the pressure is reduced to 0 before the sample is taken out to complete the pre-aging treatment.
6. The method for improving the coercivity of samarium cobalt magnets by ultrahigh pressure pre-aging treatment according to claim 1, characterized in that: The metal raw materials are industrial Sm, Co, Cu, Fe and Zr with a purity of more than 99.5wt%. The metal raw materials are placed in a medium-frequency vacuum induction furnace according to a proportion and smelted under argon protection to form a high-Fe alloy ingot; the alloy composition of the high-Fe alloy ingot is Sm 25 Co bla Fe x Cu 5.6 Zr 3.0 , x=19.5wt.%~23.5wt.%.
7. The method for improving the coercivity of samarium cobalt magnets by ultrahigh pressure pre-aging treatment according to claim 1, characterized in that: The preparation process of the solid solution samarium cobalt magnet comprises: The coarsely crushed and ball-milled alloy powder is pressed in a magnetic field of >10kOe, and is formed into a green embryo by cold isostatic pressing at 200MPa; the green embryo is sintered at 1180℃~1200℃ for 60min~90min under argon protection, and then solution treated at 1150℃~1170℃ for 60min to obtain a solid solution samarium cobalt magnet.
8. The method for improving the coercivity of samarium cobalt magnets by ultrahigh pressure pre-aging treatment according to claim 1, characterized in that: After obtaining the solid solution samarium cobalt magnet, before using the six-sided top press to perform pre-aging treatment on the solid solution samarium cobalt magnet, it also includes: cutting the solid solution samarium cobalt magnet into cylindrical samples by wire cutting; polishing the surface of the cylindrical sample with sandpaper to be smooth and completely covering it with a 0.01mm thick foil, then placing it in boron nitride powder for pressure molding, placing pyrophyllite, and performing pre-aging treatment using a six-sided top press.
9. The method for improving the coercivity of samarium cobalt magnets by ultrahigh pressure pre-aging treatment according to claim 8, characterized in that: The specifications of the cylindrical sample are: 5 mm in diameter and 2 mm in height.
Citation Information
Patent Citations
Preparation method of high-Hk samarium-cobalt sintered permanent magnet material
CN110473703A
A pressure heat treatment method to improve the magnetic properties of 2:17 type Sm-Co sintered magnets
CN112927920B
A method for prepare a high-performance samarium-cobalt sintered permanent magnet by ultra-high pressure heat treatment
CN109148139A